Description of a new species of Xylophis Beddome, 1878 (Serpentes: Pareidae: Xylophiinae) from the Western Ghats, India - Deepak, V.; Narayanan, Surya; Das, Sandeep; Rajkumar, K.p.; Easa, P.s.; Sreejith, K.a.; Gower, David J. (Zootaxa, 2020)
We reassessed the systematics of the Indian (semi)fossorial snake Xylophis perroteti (Duméril, Bibron & Duméril, 1854) based on morphological and DNA sequence data for type, historical, and new specimens. A population from the Anamalai Hills is distinct from broadly topotypic X. perroteti from the Nilgiri Hills (from which they are separated geographically by the lowland Palghat Gap) on the basis of both external morphology and DNA sequence data. We describe the Anamalai form as a new species, Xylophis mosaicus sp. nov. The new species is more closely related to X. perroteti than to X. stenorhynchus and X. captaini. A new key to identify the species of Xylophis is presented.